2018
DOI: 10.1155/2018/2686045
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Association of Genetic Markers in the LUZP2 and FBXO40 Genes with the Normal Variability in Cognitive Performance in the Elderly

Abstract: Cognitive performance is an important endophenotype for various neurodegenerative and neuropsychiatric traits. In the present study two genetic variants in the leucine-zipper protein (LUZP2) and the F-box 40 protein (FBXO40) genes, previously reported to be genome-wide significant for Alzheimer's diseases and schizophrenia, were examined for an association with cognitive abilities in normal elderly from the Russian population. Rs1021261 in the LUZP2 and rs3772130 in the FBXO40 were genotyped by multiplex PCR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…At present, we do not know much about the specific functions of LUZP2 and the articles about LUZP2 are very few. LUZP2 has been reported to be deleted in patients with Wilms' tumor-Aniridia-Genitourinary anomalies-mental Retardation (WAGR) syndrome, which is a scarce congenital anomaly syndrome consisting of Wilms' tumor, genital anomalies, aniridia, and mental retardation [ 7 , 8 ]. It is reported that polymorphic variants in this gene are associated with the late-onset Alzheimer's disease and schizophrenia [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, we do not know much about the specific functions of LUZP2 and the articles about LUZP2 are very few. LUZP2 has been reported to be deleted in patients with Wilms' tumor-Aniridia-Genitourinary anomalies-mental Retardation (WAGR) syndrome, which is a scarce congenital anomaly syndrome consisting of Wilms' tumor, genital anomalies, aniridia, and mental retardation [ 7 , 8 ]. It is reported that polymorphic variants in this gene are associated with the late-onset Alzheimer's disease and schizophrenia [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…LUZP2 (leucine zipper protein 2 gene), located on Chr 11p13–11p14 and encoding a leucine zipper protein, has been shown to be deleted in Wilms' tumor patients. Wilms' tumor, genital abnormalities, aniridia, and mental retardation is a rare congenital abnormality syndrome characterized by Wilms' tumor, genital deformities, aniridia, and mental retardation [ 24 , 25 ]. Furthermore, Zhao et colleagues found that LUZP2 mRNA expression is elevated in hormone-naive prostate cancer (PC) relative to normal prostate tissues, but downregulated throughout the progression from hormone-naive PC to castration-resistant PC (CRPC) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, we can project our expectations onto LUZP2 [ 34 ]. Downregulation of LUZP2 is linked to cellular senescence [5, which has been linked to a number of age-related diseases [ 13 , 14 , 15 , 16 ]. Only the brain and the adrenal glands have higher levels of LUZP2 expression [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…LUZP2 is found on Chr11p13–11p14 and encodes a leucine zipper protein, the deletion of which has been linked to low grade glioma, Alzheimer's disease, and schizophrenia [ 11 , 12 , 13 , 14 , 15 ]. Zhao et al.…”
Section: Introductionmentioning
confidence: 99%